2014
DOI: 10.1017/s0144686x14000658
|View full text |Cite
|
Sign up to set email alerts
|

The impact of migration experiences and migration identities on the experiences of services and caring for a family member with dementia for Sikhs living in Wolverhampton, UK

Abstract: This article is based upon qualitative research carried out with members of the Sikh community caring for a person with dementia. Previous research with South Asian carers of people with dementia has reported problems with both access to, and use of, health and social care services namely due to cultural and language barriers within existing services. The research reported in this article sought for an in-depth understanding of the experiences of Sikhs caring for their family member with dementia. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“… No indication of type or severity Sikh Focus groups Dates not reported Constant comparative methodology 28 Casado et al, 2015 [ 46 ] USA (Urban) Caregivers 23 Care-givers of people with dementia symptoms. No indication of type or severity Korean American Focus groups Dates not reported Thematic analysis 29 Jutlla, 2015 [ 47 ] UK (Urban) Carers (12) Carers of a family member with dementia. No indication of type or severity Sikh Interviews Dates not reported Constructivist grounded theory 30 Mukadam et al, 2015 [ 48 ] UK (Urban) General public (53) People without a known diagnosis of dementia, with or without experience of caring for people with dementia South Asian Focus groups & interviews Dates not reported Interpretative phenomenological analysis …”
Section: Resultsmentioning
confidence: 99%
“… No indication of type or severity Sikh Focus groups Dates not reported Constant comparative methodology 28 Casado et al, 2015 [ 46 ] USA (Urban) Caregivers 23 Care-givers of people with dementia symptoms. No indication of type or severity Korean American Focus groups Dates not reported Thematic analysis 29 Jutlla, 2015 [ 47 ] UK (Urban) Carers (12) Carers of a family member with dementia. No indication of type or severity Sikh Interviews Dates not reported Constructivist grounded theory 30 Mukadam et al, 2015 [ 48 ] UK (Urban) General public (53) People without a known diagnosis of dementia, with or without experience of caring for people with dementia South Asian Focus groups & interviews Dates not reported Interpretative phenomenological analysis …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the article by Jutlla looked at the experiences of 12 Sikh carers, caring for a family member with dementia, in Wolverhampton. 23 In particular, they looked at the influences of migration experiences and migration identities. They found that knowledge of a person’s background and experiences is important for understanding how they then experience health services and caring roles.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven papers brought up the issue of there being a limited catchment area in terms of population numbers to recruit Afro-Caribbean, Chinese, and South Asian participants from (Beattie et al, 2005;Bhatkal & Shah, 2004;Haider & Shah, 2004;Jutlla, 2015;La Fontaine et al, 2007;McCracken et al, 1997;Morgan & Crowder, 2003;Mukadam et al, 2011;Odutoye & Shah, 1999;Uppal et al, 2014;Wilkinson et al, 2003). Three papers noted that when an Afro-Caribbean or South Asian sample was identified, potential participants often did not have a formal diagnosis.…”
Section: Diagnostic Label Of Dementiamentioning
confidence: 99%